ROBOT NAVIGATION USING CAMERA BY IDENTIFYING SIGNAGES - ABD RASHID, NOOR AISYAH (2017)
Computer vision is widely used in autonomous navigation, specifically in recognizing objects or obstacles in its surrounding. Unique images of signage placed at strategic location to give information for the directions pertaining to a desired path plan. This study looks at the use of specific shapes of signage that can be used by a mobile robot to autonomously navigate from one location to another. Camera mounted on the mobile robot will capture image of the signage and later employed edge-based contour detection algorithm to extract information from the signage. Experiments have been conducted under different environments due to the signage’s position that various from one experiment to another. The robot is able to navigate itself from start to the end point by following the signages correctly with minimal assistant. Data from ultrasonic sensor is used along with information from vision system to explore the surrounding.